Targeted Mutagenesis of the Tomato PROCERA Gene Using Transcription Activator-Like Effector Nucleases. Issue 3 (12th September 2014) - Lor, Vai S.; Starker, Colby G.; Voytas, Daniel F.; Weiss, David; Olszewski, Neil E.
Abstract : Transcription activator-like effector nucleases successfully generate a heritable tomato mutant .